Rencana Strategis Biro Pemerintahan Provinsi Sumatera Barat dalam Meningkatkan Efektivitas dan Akuntabilitas Tata Kelola Pemerintahan Daerah - Wido Novaldi Gusra; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
This study develops the strategic plan for the Government Bureau of West Sumatra Province for the period as an effort to enhance the effectiveness and efficiency of provincial government governance. The method employed is qualitative research based on literature review and analysis of official documents related to strategic planning and bureaucratic reform. SWOT analysis is applied to identify strengths, weaknesses, opportunities, and threats faced by the government bureau. The findings highlight the need to strengthen human resources, integrate information technology, refine work procedures, and improve coordination among work units and stakeholders. The formulated strategic plan includes vision, mission, goals, targets, priority programs, and activities to support sustainable regional development and quality public services. Recommendations focus on improving HR capacity, bureaucratic innovation, and effective monitoring systems to achieve transparent and accountable governance.